Performance appraisal of Trichoderma viride based novel tablet and powder formulations for management of Fusarium wilt disease in chickpea - Pradhan, Prakash Chandra; Mukhopadhyay, Arkadeb; Kumar, Randeep; Kundu, Aditi; Patanjali, Neeraj; Dutta, Anirban; Kamil, Deeba; Bag, Tusar Kanti; Aggarwal, Rashmi; Bharadwaj, Chellapilla; Singh, P. K.; Singh, Anupama (Frontiers in Plant Science, 2022)
To develop a Trichoderma viride-based biocontrol program for Fusarium wilt disease in chickpea, a choice of the quality formulation is imperative. In the present study, two types of formulations i.e. powder for seed treatment (TvP) and tablet for direct application (TvT) employing T. viride as the biocontrol agent have been evaluated to control the chickpea wilt under field condition at three dosages i.e. recommended (RD), double of recommended (DD) and half of recommended (1/2 RD). Screening study for the antagonistic fungi strain based on volatile and non-volatile bioassays revealed T. viride ITCC 7764 as the most potential among the test five strains (ITCC 6889, ITCC 7204, ITCC 7764, ITCC 7847, ITCC 8276), and further was used to develop the TvP and TvT formulations. Gas Chromatography-Mass Spectrometry (GC-MS) analysis of volatile organic compounds (VOCs) of T. viride strain confirmed the most abundance compositions comprising octan-3-one (13.92%), 3-octanol (10.57%) and 1-octen-3-ol (9.40%) in the most potential T. viride 7764. Further physic-chemical characterization by standard Collaborative International Pesticides Analytical Council (CIPAC) methods revealed the optimized TvP formulation to be free flowing at pH 6.50 and density of 0.732 g cm-3. While, the TvT formulation showed a pH value of 7.16 and density of 0.0017 g cm-3 for complete disintegration time of 22.5 min. The biocontrol potential of TvP formulation was found to be superior to that of TvT formulation in terms of both seed germination and wilt incidence in chickpea under field condition. However, both the developed formulations (TvP and TvT) expressed greater bioefficacy as compared to the synthetic fungicide (Carbendazim 50% WP) and the conventional talc-based formulation. Further research should be carried out on the compatibility of the developed products with other agrochemicals of synthetic or natural origin to develop integrated disease management (IDM) schedule in chickpea.